Posterior spinal cord shift does not affect surgical outcomes after muscle-preserving selective laminectomy. (April 2018) - Nori, Satoshi; Shiraishi, Tateru; Aoyama, Ryoma; Ninomiya, Ken; Yamane, Junichi; Kitamura, Kazuya; Ueda, Seiji
Highlights: The number of operated laminae was the greatest predictor of posterior shift. The magnitude of posterior shift never affected the functional recovery. Extensive decompression is not always necessary for cervical compressive myelopathy. Abstract: Postoperative posterior spinal cord shift (PSS) has been considered a required radiographic endpoint of posterior decompression procedures. To achieve PSS, laminoplasty for cervical compressive myelopathy (CCM) has been consecutively performed on four or more laminae (C2–C7, C3–C7, or C3–C6). However, the clinical significance of PSS remains controversial. By selecting the surgically treated laminae, selective laminectomy (SL) can achieve adequate decompression without disturbing the extensor musculature and facet joints. The clinical features and radiological findings from 162 patients with CCM whose decompression included C4/5 level were investigated. The postoperative C2–C7 angle, PSS at C4/5 level, and laminectomy width were measured. Radiologic factors affecting PSS and the relationship between PSS and functional outcome were analyzed. Smaller PSS was observed in cases involving two or fewer consecutive laminectomies than in cases involving three or more consecutive laminectomies. The number of consecutive laminae (CLs) surgically treated and the postoperative C2–C7 angle correlated with PSS. Multiple linear regression analyses showed that the number of surgically treated CLs was the greatest predictor of PSS. No correlation was observed between PSS and the recovery rate (RR) of the Japanese Orthopaedic Association (JOA) score; RR of the JOA score was not affected even in patients with no PSS. PSS was affected by the number of CLs surgically treated and the postoperative C2–C7 angle. The magnitude of PSS never affected the RR of JOA score after SL. Therefore, for patients with CCM, PSS is not mandatory to obtain satisfactory functional recovery.